Education 4.0: A view from different digital proposals - Montoya-Múnera, Edwin; Aguilar, Jose; Monsalve-Pulido, Julián Alberto; Jiménez-Narváez, Marvin; Varela-Tabares, Daniela; Montoya-Jaramillo, Edwin; Salazar, Camilo; Tabares, Marta; Vallejo, Paola; Trefftz, Helmuth; Esteban, Pedro Vicente; Vega, Juan Sebastián; et al. (2020)
This book presents how 4.0 technologies enable a highly participatory and dialogic education, where students of different levels have the possibility of learning and training in their discipline while developing soft skills and, at the same time, the teachers can follow the development and evolution of these capacities and the purposes expected in the courses. Given the variety of courses modalities that are currently offered (e-learning, b-learning, m-learning, blended learning, among others), the applications presented in each chapter, as well as the appropriation of technologies for the enrichment of the students' cognitive and social skills, are an opportunity to explore new perspectives and approaches to Education 4.0.
Keywords: Tecnología educativa; Innovaciones educativas; Realidad aumentada en educación; Inteligencia artificial; Aplicaciones en educación; e-learning Environments; Smart classroom; Teaching-Learning Process